PROSEDUR PENINGKATAN PENANGANAN KESEHATAN DAN KESELAMATAN KERJA PADA PT. X - Priscilla Modena; I Wayan Sukania (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Occupational health and safety or K3 is something that should not be overlooked in an activity that involves human resources with their work. Similar to work accidents that often occur in a job that involves physical activity in it, it can be anticipated by applying K3 and SOP for each work activity. PT. X is engaged in offset printing and carrying out the production process using machines every day will certainly pose a risk of work accidents. Awareness of factory employees in the implementation of K3 which is still relatively low causes work accidents to occur every year such as scratched fingers, pinched fingers, scratched palms, dropped forklift loads, burned hands and slipping forklift operators. Therefore, by using a fishbone diagram or cause and effect diagram and then by elaborating through a fishbone diagram analysis table, the causes of work accidents at PT. X are obtained. The company is advised to make improvements by increasing K3 awareness, routine machine maintenance, and updating K3 every year.